(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: Diagnosis of cervical lesions has become very important to reduce morbidity and mortality related to cervical cancer. In most developed countries, screening programmes for early detection of preclinical cervical cancer has proven to be very useful and have contributed to improved results of treatment. The lack of understanding of cervical cancer among people and policy makers contributes to the burden of cervical cancer on India’s health system. Cervical cancer is easily preventable by detecting early lesions and initiating appropriate programs to treat them. Aim and Objective: To detect premalignant and malignant lesions with traditional Pap smear cytology plus colposcopic guided biopsies has high diagnostic accuracy. Methodology: This study was carried out at Santosh Medical College and Hospital, Ghaziabad, U.P in the Department of Pathology and Obstetrics and Gynaecology during a period of one and half year. We took a total of 200 patients presenting with clinical symptomatology in the Obstetrics and Gynaecology department and performed Pap smear on all 200 cases. Result: There were 52(26%) patients turned out to be normal on Pap smear and 148(74%) cases were found to be abnormal. Out of these abnormal cases 42(21%) cases appeared either Dysplastic or Neoplastic on Pap smear. Conclusion: The Pap smears sensitivity was 76.2%, but its specificity was a magnificent 100%. PAP smear cytology has a diagnostic accuracy of 88.3%.